New Class of Attitude Controllers Guaranteed to Converge within Specified Finite-Time

Abstract

This paper introduces a new class of finite-time feedback controllers for rigid-body attitude dynamics subject to full actuation. The control structure is Lyapunov-based and is designed to regulate the configuration from an arbitrary initial state to any prescribed final state within user-specified finite transfer-time. A salient feature here is that the synthesis of the control structure is explicit, i.e., given the transfer-time time, the feedback-gains are explicitly stated to satisfy the convergence specifications. A major contrast between this work and others in the literature is that instead of resorting to feedback-linearization (to get to the so-called normal form), our approach efficiently marries the process of designing time-varying feedback gains with the logarithmic Lyapunov function for attitude kinematics based on the Modified Rodrigues Parameters representation. Saliently, this finite-time solution extends nicely for accommodating trajectory tracking objectives and possesses robustness with respect to bounded external disturbance torques. Numerical simulations are performed to test and validate the performance and robustness features of the new control designs.

This is a preview of subscription content, log in to check access.

Fig. 1
Fig. 2
Fig. 3
Fig. 4

Notes

  1. 1.

    We use the property \(a\boldsymbol {b}^{T}\boldsymbol {c} \leq \frac {1}{2}\left (\begin {array}{llll} a^{2} ||\boldsymbol {b}||^{2} + ||\boldsymbol {c}||^{2} \end {array}\right ), \forall a \in \mathbb {R}_{>0}, \boldsymbol {b} \in \mathbb {R}^{n}, \boldsymbol {c} \in \mathbb {R}^{n}, n \in \mathbb {Z}_{>0}\).

References

  1. 1.

    Athans, M., Falb, P.L.: Optimal Control: An Introduction to the Theory and its Applications. Courier Corporation (2013)

  2. 2.

    Slotine, J.-J.E., Li, W., et al.: Applied Nonlinear Control, vol. 199. Prentice Hall, Englewood Cliffs (1991)

    Google Scholar 

  3. 3.

    Bhat, S.P., Bernstein, D.S.: Finite-time stability of continuous autonomous systems. SIAM J. Control. Optim. 38(3), 751–766 (2000)

    MathSciNet  Article  Google Scholar 

  4. 4.

    Song, Y., Wang, Y., Holloway, J., Krstic, M.: Time-varying feedback for regulation of normal-form nonlinear systems in prescribed finite time. Automatica 83, 243–251 (2017)

    MathSciNet  Article  Google Scholar 

  5. 5.

    Bryson, A., Ho, Y.-C.: Applied Optimal Control: Optimization, Estimation, and Control (Revised Edition). Taylor & Francis, Levittown (1975)

    Google Scholar 

  6. 6.

    Tsiotras, P.: New Control Laws for the Attitude Stabilization of Rigid Bodies. Automatic Control in Aerospace 1994 (Aerospace Control’94), pp. 321–326. Elsevier (1995)

  7. 7.

    Junkins, J.L., Akella, M.R., Robinett, R.D.: Nonlinear adaptive control of spacecraft maneuvers. J. Guid. Control Dyn. 20(6), 1104–1110 (1997)

    Article  Google Scholar 

  8. 8.

    Shuster, M.D.: A survey of attitude representations. Navigation 8(9), 439–517 (1993)

    MathSciNet  Google Scholar 

  9. 9.

    Khalil, H.K.: Nonlinear Systems. New Jewsey, Prentice Hall (2002)

    Google Scholar 

  10. 10.

    Wen, J.-Y., Kreutz-Delgado, K.: The attitude control problem. IEEE Trans. Autom. control 36(10), 1148–1162 (1991)

    MathSciNet  Article  Google Scholar 

  11. 11.

    Chatuverdi, N., Sanyal, A.K., McClamroch, N.H.: Rigid-body attitude control using rotation matrices for continuous, singularity-free control laws. IEEE Control. Syst. Mag. 31(8), 30–51 (2011)

    MathSciNet  MATH  Google Scholar 

  12. 12.

    Cemenska, J.: Sensor Modelling and Kalman Filtering Applied to Satellite Attitude Determination. University of California at Berkeley, PhD thesis (2004)

    Google Scholar 

Download references

Author information

Affiliations

Authors

Corresponding author

Correspondence to Marcelino M. de Almeida.

Additional information

Publisher’s Note

Springer Nature remains neutral with regard to jurisdictional claims in published maps and institutional affiliations.

Appendices

Appendix A

In this section, we prove that if:

$$ \mu^{\lambda}(t) \ln \left( \begin{array}{llll} 1 + \boldsymbol{\sigma}^{T}(t) \boldsymbol{\sigma}(t) \end{array}\right) \leq V_{0}(0)\exp \left[\begin{array}{llll} -kt_{f}\cdot\bar{\mu}(t) \end{array}\right], $$
(55)

then \(\mu ^{\alpha _{1}} \boldsymbol {\sigma } \in L_{\infty }, \forall \alpha _{1} \in \mathbb {R}\).

Starting from Eq. 55, we use the definition \(\bar {\mu }(t) \triangleq \mu (t) - 1\) to get:

$$ \begin{array}{@{}rcl@{}} \mu^{\lambda}(t) \ln \left( \begin{array}{llll} 1 + \boldsymbol{\sigma}^{T}(t) \boldsymbol{\sigma}(t) \end{array}\right) &\leq& V_{0}(0)\exp \left[\begin{array}{llll} -kt_{f}\cdot(\mu(t) - 1) \end{array}\right] \\ &= &V_{0}(0)e^{kt_{f}} \exp \left[\begin{array}{llll} -kt_{f} \cdot \mu(t) \end{array}\right] \\ &= &\alpha_{2} \exp \left[\begin{array}{llll} -kt_{f} \cdot \mu(t) \end{array}\right], \end{array} $$
(56)

where \(\alpha _{2} \triangleq V_{0}(0)e^{kt_{f}} > 0\).

Defining \(\beta (t) \triangleq \exp \left [\begin {array}{llll} -kt_{f}\cdot \mu (t) \end {array}\right ]\), it follows that:

$$ \begin{array}{@{}rcl@{}} \mu^{\lambda}(t)\ln\left( \begin{array}{llll} 1 + \boldsymbol{\sigma}^{T}(t) \boldsymbol{\sigma}(t) \end{array}\right) &\leq& \alpha_{2} \beta(t) \\ \ln \left( \begin{array}{llll} 1 + \boldsymbol{\sigma}^{T}(t) \boldsymbol{\sigma}(t) \end{array}\right) &\leq& \alpha_{2} \mu^{-\lambda}(t)\beta(t) \\ 1 + \boldsymbol{\sigma}^{T}(t) \boldsymbol{\sigma}(t) &\leq& \exp \left[\begin{array}{llll} \alpha_{2} \mu^{-\lambda}(t)\beta(t) \end{array}\right] \\ \boldsymbol{\sigma}^{T}(t) \boldsymbol{\sigma}(t) &\leq &\exp \left[\begin{array}{llll} \alpha_{2} \mu^{-\lambda}(t)\beta(t) \end{array}\right] - 1 \\ \mu^{2\alpha_{1}}(t)\boldsymbol{\sigma}^{T}(t) \boldsymbol{\sigma}(t) &\leq& \mu^{2\alpha_{1}}(t) \left[\begin{array}{llll} \exp \left[\begin{array}{llll} \alpha_{2} \mu^{-\lambda}(t)\beta(t) \end{array}\right] - 1 \end{array}\right] \\ ||\mu^{\alpha_{1}}(t)\boldsymbol{\sigma}(t)||^{2} &\leq& \frac{\exp \left[\begin{array}{llll} \alpha_{2} \mu^{-\lambda}(t)\beta(t) \end{array}\right] - 1} {\mu^{-2\alpha_{1}}(t)}. \end{array} $$
(57)

In order to show that the signal \(f(t) \triangleq ||\mu ^{\alpha _{1}}(t)\boldsymbol {\sigma }(t)||^{2}\) is bounded, we need to evaluate the limit as ttf. Taking the limit on both sides:

$$ \lim\limits_{t \to t_{f}}f(t) \leq \lim\limits_{t \to t_{f}}\frac{\exp \left[\begin{array}{llll} \alpha_{2} \mu^{-\lambda}(t)\beta(t) \end{array}\right] - 1} {\mu^{-2\alpha_{1}}(t)}. $$
(58)

The above limit can be rewritten as:

$$ \lim\limits_{t \to t_{f}}f(t) \leq \lim\limits_{\mu \to \infty}\frac{\exp \left[\begin{array}{llll} \alpha_{2} \mu^{-\lambda} \exp \left[\begin{array}{llll} -k\cdot t_{f}\cdot\mu \end{array}\right] \end{array}\right] - 1} {\mu^{-2\alpha_{1}}}. $$
(59)

Assuming that λ < 2α1, Lemmas 1 and 2 are used to prove that the right-hand side of Eq. 59 is equal to zero, implying that \(||\mu ^{\alpha _{1}}(t)\boldsymbol {\sigma }(t)||^{2} \in L_{\infty }, \forall \alpha _{1} > \lambda /2\). In addition, since \(||\mu ^{\eta _{1}}(t)\boldsymbol {\sigma }(t)||^{2} \leq ||\mu ^{\eta _{2}}(t)\boldsymbol {\sigma }(t)||^{2}\), for η1η2, then \(||\mu ^{\alpha _{1}}(t)\boldsymbol {\sigma }(t)||^{2} \in L_{\infty }, \forall \alpha _{1} \in \mathbb {R}\).

Lemma 1

For any finite real constantsα1≠ 0,α2 > 0,γ1 > 0,γ2 > 0, then:

$$ \lim\limits_{x \to 0+} \alpha_{1} x^{-\gamma_{1}}exp\left[\begin{array}{llll} -\alpha_{2} x^{-\gamma_{2}} \end{array}\right] = 0. $$
(60)

Proof

Making the substitution \(y = x^{-\gamma _{2}}\), then:

$$ \lim\limits_{x \to 0+} \alpha_{1} x^{-\gamma_{1}}exp\left[\begin{array}{llll} -\alpha_{2} x^{-\gamma_{2}} \end{array}\right] = \lim\limits_{y \to \infty} \alpha_{1} y^{\gamma_{3} + \gamma_{4}}e^{-\alpha_{2} y}, $$
(61)

where \(\gamma _{3} \in \mathbb {N} \triangleq \lfloor \gamma _{1}/\gamma _{2} \rfloor \) and \(\gamma _{4} \in [0, 1) \triangleq \gamma _{1}/\gamma _{2} - \gamma _{3}\).

One can notice that the limit in Eq. 61 is a product of zero with , which can be solved for by using L’Hospital’s rule. Defining \(\gamma _{5} \triangleq \gamma _{3} + \gamma _{4}\), we apply L’Hospital’s rule γ3 times, leading to:

$$ \begin{array}{@{}rcl@{}} \lim_{y \to \infty} \alpha_{1} y^{\gamma_{5}}e^{-\alpha_{2} y} &= &\lim\limits_{y \to \infty} -\alpha_{1} \alpha_{2} \gamma_{5} y^{\gamma_{5}-1}e^{-\alpha_{2} y} \\ &= &\lim\limits_{y \to \infty} \alpha_{1} {\alpha_{2}^{2}} \gamma_{5}(\gamma_{5}-1) y^{\gamma_{5}-2}e^{-\alpha_{2} y} \\ &= &\cdots \\ &= &\lim\limits_{y \to \infty} (-1)^{\gamma_{3}}\alpha_{1} \alpha_{2}^{\gamma_{3}} \gamma_{5}(\gamma_{5}-1)\cdots(\gamma_{5}-\gamma_{3}) y^{\gamma_{4}}e^{-\alpha_{2} y}. \end{array} $$
(62)

If γ4 = 0, then the proof is complete. However, if γ4 ∈ (0, 1), then we need to use L’Hospital’s rule one more time:

$$ \begin{array}{@{}rcl@{}} \lim\limits_{y \to \infty} \alpha_{1} y^{\gamma_{5}}e^{-\alpha_{2} y} &= &\lim\limits_{y \to \infty} (-1)^{\gamma_{3}+1}\alpha_{1} \alpha_{2}^{\gamma_{3}+1} \gamma_{5}(\gamma_{5}-1)\cdots(\gamma_{5}-\gamma_{3})\gamma_{4} y^{\gamma_{4}-1}e^{-\alpha_{2} y} = 0. \end{array} $$
(63)

Lemma 2

For any finite real constantsα1 > 0,α2 > 0, and0 < γ1γ2 < γ3,then\(\lim _{x \to \infty }f(x) = 0\),where:

$$ f(x) = \frac{\exp \left[\begin{array}{llll} \alpha_{1} x^{-\gamma_{2}}\exp\left[\begin{array}{llll} -\alpha_{2} x^{\gamma_{1}} \end{array}\right] \end{array}\right] - 1} {x^{-\gamma3}}. $$
(64)

Proof

Defining \(y \triangleq x^{-\gamma _{3}}\), we have that \(y^{-\gamma _{4}} = x^{\gamma _{1}}\), and \(y^{\gamma _{5}} = x^{-\gamma _{2}}\), where \(\gamma _{4} \triangleq \frac {\gamma _{1}}{\gamma _{3}}\) and \(\gamma _{5} \triangleq \frac {\gamma _{2}}{\gamma _{3}}\). Since 0 < γ1γ2 < γ3, then 0 < γ4γ5 < 1. The limit can be rewritten as:

$$ \lim\limits_{x \to \infty}f(x) = \lim\limits_{y \to 0^{+}}f(y) = \frac{\exp \left[\begin{array}{llll} \alpha_{1} y^{\gamma_{5}}\exp\left[\begin{array}{llll} -\alpha_{2} y^{-\gamma_{4}} \end{array}\right] \end{array}\right] - 1} {y}. $$
(65)

For notation simplicity, we define \(\beta (y) \triangleq \exp \left [\begin {array}{llll} -\alpha _{2} y^{-\gamma _{4}} \end {array}\right ]\), leading to:

$$ \lim\limits_{y \to 0^{+}}f(y) = \lim\limits_{y \to 0^{+}}\frac{\exp \left[\begin{array}{llll} \alpha_{1} y^{\gamma_{5}} \beta(y) \end{array}\right] - 1} {y}. $$
(66)

It is straightforward to see that \(\lim _{y \to 0^{+}}\beta (y) = 0\) and that \(\lim _{y \to 0^{+}}e^{\alpha _{1} y^{\gamma _{5}} \beta (y)} = 1\). Since this limit is a ratio of zero with zero, we can use L’Hospital’s rule to show that the right-hand side of Eq. 66 converges to zero as y → 0+. We define the numerator signal as:

$$ n(y) \triangleq e^{\alpha_{1} y^{\gamma_{5}}\beta(y)} - 1. $$
(67)

Clearly, it is sufficient to prove that if \(\lim _{y \to 0^{+}}\frac {dn(y)}{dy} = 0\), then

$$ \lim\limits_{y \to 0^{+}}\frac{e^{\alpha_{1} y^{\gamma_{5}}\beta(y)} - 1} {y} = 0, $$
(68)

implying that \(\lim _{y \to 0^{+}}f(y) = 0\). Using the notation \(f^{\prime } \triangleq \frac {\partial f}{\partial y}\) the derivative of n(y) is given by:

$$ n^{\prime}(y) = \alpha_{1} \left( \begin{array}{llll} \frac{\gamma_{5}}{y^{\gamma_{6}}}\beta(y) + y^{\gamma_{5}}\beta^{\prime}(y) \end{array}\right)e^{\alpha_{1} y^{\gamma_{5}}\beta(y)}, $$
(69)

where γ6 > 0 is defined as \(\gamma _{6} \triangleq 1 - \gamma _{5}\). Given that

$$ \beta^{\prime}(y) = \alpha_{2} \gamma_{4} y^{-\gamma_{4} - 1}\exp \left[\begin{array}{llll} -\alpha_{2} y^{-\gamma_{4}} \end{array}\right] = \frac{\alpha_{2} \gamma_{4}}{y^{\gamma_{7}}}\beta(y), $$
(70)

for \(\gamma _{7} \triangleq 1 + \gamma _{4} > 1\), we can substitute Eq. 70 into Eq. 69:

$$ n^{\prime}(y) = \alpha_{1} \left( \begin{array}{llll} \frac{\gamma_{5}}{y^{\gamma_{6}}}\beta(y) + \frac{\alpha_{2} \gamma_{4}}{y^{\gamma_{7} - \gamma_{5}}}\beta(y) \end{array}\right)e^{\alpha_{1} y^{\gamma_{5}}\beta(y)}. $$
(71)

One should note that since γ7 > 1 and 0 < γ5 < 1, then γ7γ5 > 0. Using Lemma 1 and the definition \(\beta (y) \triangleq \exp \left [\begin {array}{llll} -\alpha _{2} y^{-\gamma _{4}} \end {array}\right ]\), then:

$$ \left\{\begin{array}{llll} \lim_{\xi \to 0^{+}} \frac{\gamma_{5}}{y^{\gamma_{6}}}\beta(y) = 0, \\ \lim_{\xi \to 0^{+}} \frac{\alpha_{2} \gamma_{4}}{y^{\gamma_{7} - \gamma_{5}}}\beta(y) = 0 \end{array}\right.. $$
(72)

Remembering that \(\lim _{y \to 0^{+}}\beta (y) = 0\), and that \(\lim _{y \to 0^{+}}e^{\alpha _{1} y^{\gamma _{5}}\beta (y)} = 1\), then \(\lim _{y \to 0^{+}} n^{\prime }(y) = 0\), which implies that \(\lim _{x \to \infty }f(x) = 0\).

Appendix B

In this section, we show that the inequality

$$ \mu^{\lambda}(t)\ln(1 + \boldsymbol{\sigma}^{T}(t)\boldsymbol{\sigma}(t)) \leq \bar{V}, $$
(73)

for a constant \(\bar {V} > 0\), implies that μλ/2σL and that \(\lim _{t \to t_{f}}\mu ^{\rho }(t)\boldsymbol {\sigma }(t) = 0, \forall \rho < \lambda /2\).

Starting from Eq. 73, we have that:

$$ \begin{array}{@{}rcl@{}} \boldsymbol{\sigma}^{T}(t)\boldsymbol{\sigma}(t) &\leq& \exp \left[\begin{array}{llll} \bar{V}\mu^{-\lambda}(t) \end{array}\right] - 1 \end{array} $$
(74)
$$ \begin{array}{@{}rcl@{}} \mu^{\lambda}(t)\boldsymbol{\sigma}^{T}(t)\boldsymbol{\sigma}(t) &\leq& \mu^{\lambda}(t) \left[\begin{array}{llll} \exp \left[\begin{array}{llll} \bar{V}\mu^{-\lambda}(t) \end{array}\right] - 1 \end{array}\right] \end{array} $$
(75)
$$ \begin{array}{@{}rcl@{}} ||\mu^{\lambda/2}(t)\boldsymbol{\sigma}(t)||^{2} &\leq& \frac{\exp \left[\begin{array}{llll} \bar{V}\mu^{-\lambda}(t) \end{array}\right] - 1}{\mu^{-\lambda}(t)}. \end{array} $$
(76)

In order to show that the signal \(f(t) \triangleq ||\mu ^{\lambda /2}(t)\boldsymbol {\sigma }(t)||^{2}\) is bounded, we need to evaluate the limit as ttf. Taking the limit on both sides:

$$ \lim\limits_{t \to t_{f}}f(t) \leq \lim\limits_{t \to t_{f}} \frac{\exp \left[\begin{array}{llll} \bar{V}\mu^{-\lambda}(t) \end{array}\right] - 1}{\mu^{-\lambda}(t)}. $$
(77)

Assuming λ > 0, the above limit can be rewritten as:

$$ \lim\limits_{t \to t_{f}}f(t) \leq \lim\limits_{\mu \to \infty} \frac{\exp \left[\begin{array}{llll} \bar{V}\mu^{-\lambda} \end{array}\right] - 1}{\mu^{-\lambda}}. $$
(78)

Defining \(\xi (t) \triangleq \mu ^{-\lambda }(t)\), we have that:

$$ \lim\limits_{t \to t_{f}}f(t) \leq \lim\limits_{\xi \to 0^{+}} \frac{\exp \left[\begin{array}{llll} \bar{V}\xi \end{array}\right] - 1}{\xi}. $$
(79)

Since the above limit is a ratio of zero with zero, we can use L’Hospital’s rule:

$$ \begin{array}{@{}rcl@{}} \lim\limits_{t \to t_{f}}f(t) &\leq& \lim\limits_{\xi \to 0^{+}} \frac{\frac{d}{d\xi} \left[\begin{array}{llll} \exp \left[\begin{array}{llll} \bar{V}\xi \end{array}\right] - 1 \end{array}\right]}{\frac{d}{d\xi}\xi} \end{array} $$
(80)
$$ \begin{array}{@{}rcl@{}} &=& \lim\limits_{\xi \to 0^{+}} \bar{V} \exp \left[\begin{array}{llll} \bar{V}\xi \end{array}\right] \end{array} $$
(81)
$$ \begin{array}{@{}rcl@{}} &=& \bar{V} \end{array} $$
(82)

Therefore, \(f(t) \triangleq ||\mu ^{\lambda /2}(t)\boldsymbol {\sigma }(t)||^{2}\) is bounded, i.e., μλ/2σL. Also, since \(||\mu ^{\lambda /2}(t)\boldsymbol {\sigma }(t)||^{2} \leq \bar {V}\), then for any 𝜖 > 0 and constant ρ such that 2𝜖 + ρ = λ/2 we have that \(||\mu ^{\rho }\boldsymbol {\sigma }(t)||^{2} \leq \mu ^{-\epsilon }(t)\bar {V}\), implying that \(\lim _{t \to t_{f}} ||\mu ^{\rho }\boldsymbol {\sigma }(t)||^{2} = 0\).

Rights and permissions

Reprints and Permissions

About this article

Verify currency and authenticity via CrossMark

Cite this article

de Almeida, M.M., Akella, M.R. New Class of Attitude Controllers Guaranteed to Converge within Specified Finite-Time. J Astronaut Sci 67, 552–570 (2020). https://doi.org/10.1007/s40295-019-00180-5

Download citation

Keywords

  • Attitude tracking
  • Finite-time control
  • Disturbance rejection
  • Modified Rodrigues parameters